(The Processing of Effevescent Ginger Extract (Zingiber officinale Rosc.) Extract. - Tiurlan Farida Hutajulu; Eddy Sapto Hartanto (Balai Besar Industri Agro, 2006)
The research about the processing of ginger ekstrac (Zingiber Officinale Rose)Effervescent had been conducted by using water solvent with granulation and formulation of sugar,citric acid and sodium bicarbonate.In the premiliminary research 3 (three)type of powder ginger has been treated from ginger extract and sugar with each comparation 70:80 60:90 and 50:100.From those three types of powder ginger that form a granula/crytal which is comparation of ginger extract and sugar 50:100.On the main research powder ginger had been used to create effervescent formula which is the mixture of powder ginger,citric acid,sodium bicarbonate and aspartam with specific comparation.The best result treated from the research of Effervescent product is C formula,which is the comparation of powder ginger :citric acid:sodium bicarbonate:aspartam =92:6:2:0,005.The organoleptic test(taste,colour,smell and apperance)with hedonic method by 15 panelists resulted in C formula as most favourable.Based on observation of effervescent product during incubation (0,14,28,56 days)to sugar concentration is showed tend to descreased,however,the moisture was increased,meanwhile ash content and insoluble matter were not changed.